Pengaruh Pengungkapan Sustainability Report Dan Kualitas Audit Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur 2016-2020 - Adela Putri Widyadi; Jacobus Widiatmoko (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Company information disclosure is currently an additional value for companies that disclose it. This study was conducted to find out the influence of Sustainability Report and Audit Quality disclosure on the Firm Value with the variable control profitability, leverage, and size. Population in this study was the manufacturing sector companies which has been listing on the Indonesia Stock Exchange from 2016 to 2020. There were 90 samples determined by the purposive sampling technique and have fulfilled the established criteria. Regression test in this study used multiple linear regression. Research results were obtained that: 1) Sustainability Report has positive and significant effect on firm value. 2) Audit quality has a positive and significant effect on firm value.